The critical role of Toll-like receptor-mediated signaling in cancer immunotherapy - Xue Chen; Yunxiao Zhang; Yao Fu (Elsevier, 2022)
Toll-like receptors (TLR) play a dual regulatory role in the tumor microenvironment (TME). TLR agonists (TLRa) elicit both innate and adaptive immune responses to achieve anti-tumor effects, whereas the inflammatory response induced by TLRa contributes to the immune escape of tumor cells. Preliminary evidences suggest that TLRa result in antitumor effects and can be explored as vaccine adjuvants in both preclinical and clinical models, however, only a few obtained the FDA approval for clinical studies. Meanwhile, TLR antagonists are explored as anti-inflammatory therapeutics in combination with various antitumor therapies. This article reviews the biological functions of TLRs and their differential expression in the TME, summarizes the latest data on the application of both agonists and antagonists as immunomodulator in cancer immunotherapy with a particular focus on the TLRa as single immune modulator or combination therapies.